Investigation of Neem Fatty Acid Ethyl Ester for Electric Power Generation - G. Vijaya Gowri; M. Kannan; A. Murugesan (Institute of Advanced Engineering and Science, 2015)
Producing an efficient alternative renewable fuel for power generation is the solution for today’s power crisis. As the oil prices are increasing day- by- day and the fossil fuels are depleting, why to rely on the fossil fuels for energy?. One of the alternative fuels is bio-fuel which can be obtained from sewage, garbage and waste vegetable oils which would otherwise be difficult to dispose leading to pollution. Biodiesel is a substitute for petroleum-based diesel which is derived from vegetable oils by the process of trans-esterification. Biodiesel is prevalently used as automobile fuel. Ethyl esters produced by trans-esterification can be used for rural electrification. In this paper, the electrified quality output obtained using different blends of ethyl ester with diesel and the efficiencies for each blend and pure diesel are studied and the results show that power generation using ethyl ester for rural population will be efficient, reliable and economical.